Взаимосвязь устойчивости нервных центров и типов вегетативной нервной системы - Садовская, Ю.Я.; Лукавенко, А.В.; Хрипунова, Л.Д.; Зыгарь, О.Н. (Таврический медико-биологический вестник, 2010)
Взаємозв’язок стійкості нервових центрів і типів вегетативної нервової системи. У статті описані результати дослідження ступеня стійкості нервових центрів при певному типі вегетативної нервової системи у студентів. Була розроблена двухступенчатая зміцнююча програма для тренування нервових центрів і наближення вегетативного дисбалансу до норми. In the article are described the results of research of the degree of resistance of the NS(nervous system) at a definite type of vegetative NS of students. 90 students were experimented. Two-level enforcing program for training of nervous centers and approaching the vegetative disbalance to the norm was developed.